A Scoping Review: Comparison of Cigarette Consumption among Adolescents in Asia - Sella Puspita Sari; Made Adhyatma Prawira Natha Kusuma; Syamsulhuda Budi Musthofa; Nurjazuli (Universitas Airlangga, 2025)
Background: Adolescent smoking has a significant impact on public health. Adolescent smoking is a global health problem that requires serious attention since it causes long-term public health impacts, including an increased risk of chronic diseases. Objectives: This review aims to examine the comparisons and factors affecting adolescent cigarette consumption in Asian countries. Methods: This study used a scoping review method to explore and understand the level of cigarette consumption among youth in various Asian countries. This study used various sources from PubMed, Google Scholar, and Springer Link databases. The keywords used in this article include youth cigarette consumption, Asia, Factors, Prevalence, and Comparison. This review was conducted on 400 articles that were screened and analyzed into 10 articles. The selected articles were free and full text in English, within five years between 2019 and 2023. The selected articles covered various fields namely medicine, health, healthcare, environmental science, and social science. The selected articles provided data from Malaysia, Japan, China, Taiwan, Indonesia, and East Timor. Results: The results are used to detail a comparison of youth cigarette consumption in Asia countries, thereby supporting more effective and contextualized public health. Conclusion: We identified that personal, environmental, and societal factors are the main causes of youth cigarette consumption in Asia.